1998
DOI: 10.1098/rsta.1998.0237
|View full text |Cite
|
Sign up to set email alerts
|

Defect-induced spin disorder and magnetoresistance in single-crystal and polycrystal rare-earth manganite thin films

Abstract: Although theoretical understanding of doped mixed-valence manganites that exhibit colossal magnetoresistance (CMR) is still incomplete, the general observation of a systematic correlation at a given temperature between the magnetization and resistance both above and below the Curie temperature T C can provide a phenomenological basis for describing the magnetotransport response of defective or magnetically inhomogeneous materials. Defect-related changes in the local magnetization correspond to changes in spin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(35 citation statements)
references
References 27 publications
(46 reference statements)
0
35
0
Order By: Relevance
“…temperatures around T C . The MR peak near T C arises from the CMR component inside the grains (intrinsic CMR effect), whereas the low-field MR at low temperatures is due to the grain boundaries (extrinsic MR effect) [47][48][49][50][51][52][53][54]. The extrinsic MR effect has been explained in terms of spin-polarized tunneling between grains [47,53] or spin-dependent scattering of polarized electrons at the grain boundaries [48,49].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…temperatures around T C . The MR peak near T C arises from the CMR component inside the grains (intrinsic CMR effect), whereas the low-field MR at low temperatures is due to the grain boundaries (extrinsic MR effect) [47][48][49][50][51][52][53][54]. The extrinsic MR effect has been explained in terms of spin-polarized tunneling between grains [47,53] or spin-dependent scattering of polarized electrons at the grain boundaries [48,49].…”
Section: Methodsmentioning
confidence: 99%
“…6 shows the temperature dependence of the resistance at zero magnetic field for all samples. The resistance of the V-free polycrystalline sample is dominated by the grain boundaries [47][48][49][50][51][52][53][54]. The resistance of the composites is mainly affected by both of the grain size and the resistance of the FM phase, and both of the amount and the distribution of the secondary phases.…”
Section: Methodsmentioning
confidence: 99%
“…At low temperatures a large extrinsic magnetoresistance effect was observed which decays much stronger with temperature as is anticipated from the temperature dependence of the saturation magnetization. This was attributed to a reduced interfacial magnetization [7][8][9][10] and up to date no remedy to solve this problem of manganite compounds has been found. Comparative studies of the temperature dependence of the extrinsic magnetoresistance in various half-metallic oxides showed that the decay of the low-field magnetoresistance is much weaker in double perovskites of the type Sr 2 FeMoO 6 than in the manganites and CrO 2 [11].…”
Section: Introductionmentioning
confidence: 97%
“…In the polycrystalline films and bulk samples electrical transport across the grain boundaries is proposed due to spinpolarized tunneling [5] or due to spin-dependent scattering of polarized electron at the grain boundaries [4,12]. A mesoscopic magnetoresistance model based on a grain boundary region with strongly suppressed T c has also been proposed [13]. The nature of surfaces and interfaces is a central issue for the proper understanding of the grain boundary transport and magnetoresistance effect in these polycrystalline samples.…”
Section: Introductionmentioning
confidence: 98%